Design and development of latex cups collector robot V3 (mechanical) - Khor, Pey Wen (2023)

(untitled)
Rubber is widely used in the production of products such as gloves, tyres, and mattresses, and the demand for rubber products is increasing over time. Nonetheless, global rubber production has declined in recent years due to a variety of factors, including both environmental and human factors. The lack of manpower in latex collection is one of the main reasons for the reduction in rubber production. This project developed an automated robot prototype that collects latex cups in order to improve global rubber production by assisting workers in rubber plantations. The robot was designed on a mobile platform equipped with a motor-driven Five Degree of Freedom (DoF) manipulator arm, Ackermann steering, double wishbone suspension, rear-wheel drive and a latex storage tank to store the latex collected from the trees. The robot was equipped with ultrasonic sensors to locate latex cups and rubber trees so that it could move and perform tasks accurately. In addition, encoder sensor modules were used to improve the accuracy of the movements by measuring the rotational speed of the motors. The yield strength of the PLA plastic material used in developing the latex cup collector robot is 7.00 x 107N/m2 and the maximum stress of the critical parts should not exceed the maximum yield strength of the PLA plastic. The robot prototype has gone through tests such as a mobility test, a static test and a balance test to test its functionality and stability. The height of the barrier used to conduct mobility test is 10mm and 15mm. Other than that, the robot prototype has also performed test runs to validate its control system. These findings demonstrated that the prototype design is workable and capable of carrying out fundamental duties automatically on the uneven terrain of the rubber plantation.